Governor-General Leonard Wood’s neoliberal agenda of privatizing public assets stymied, 1921-1927 - Ybiernas, Vicente Angel S. (Social Science Diliman: A Philippine Journal of Society and Change; Vol 8 No 1 (2012))
After a serious fiscal and financial crisis erupted in 1920 to 1921 (in the wake of the termination of World War I), the new American Governor General to the Philippines, U.S. Army Major General Leonard Wood, promised in his inaugural address to privatize the country’s government-owned and controlled corporations such as the Philippine National Bank and the Manila Railroad Company, among others. Wood’s neoliberal agenda in the Philippines was opposed by Filipino politicians in the executive and legislative departments from the start. This key policy disagreement climaxed in the resignation en masse of Governor Wood’s Filipino cabinet and the members of the executive-legislative Council of State in 1923. The particulars of the Cabinet Crisis of 1923 —the so-called Conley Affair— however, obscured from plain sight the true gravity of the broader conflict (i.e., Filipino opposition to Wood’s agenda). Moreover, the general perception that Governor Wood’s asset privatization program was successfully blocked by the Cabinet Crisis of 1923 is inaccurate. In truth, Wood was stymied by adverse international and national market conditions from 1921 to 1923. A further delay occurred from 1924 to 1926 when Governor Wood endeavored to get the Council of State and the Filipino Legislature’s Board of Control (an oversight committee) on board his neoliberal agenda; he failed to get the support of the Filipino leaders in this regard. When Wood finally decided in 1926 to take unilateral steps, he was tied up by litigation (locally and in the United States) arising from his actions until his death from an unsuccessful brain surgery in 1927. Keywords: asset privatization, fiscal reform, patronage politics, economic heritage